Asemi-Empirical Study of the Adsorption of Some Organic Pollutants on Modified Iraqi Clays (Baghdad Science Journal, 2016)
In this work semi–empirical method (PM3) calculations are carried out by (MOPAC) computational packages have been employed to calculate the molecular orbital's energies for some organic pollutants. The long– chain quaternary ammonium cations called Iraqi Clays (Bentonite – modified) are used to remove these organic pollutants from water, by adding a small cationic surfactant so as to result in floes which are agglomerates of organobentonite to remove organic pollutants. This calculation which suggests the best surface active material, can be used to modify the adsorption efficiency of aniline , phenol, phenol deriviatives, Tri methyl glycine, ester and pecticides , on Iraqi Clay (bentonite) by comparing the theoretical results with experimental results achived in previous experimental studies between some organic pollutants and modified bentonite by (1- Hexadecyl pyridinium bromide) (HDPYBr). The theoretical calculation is made by using three surface active materials [1- (Hexadecyl pyridinium bromide) (HDPYBr), (1,12- Dipyridiniododecane dibromide) (DPYDDBr2) and Hexadecyl trimethyl ammonium bromide (HDTMA)]. Using (HDTMA) leads to the best adsorption efficiency for most pollutants involved in this study. The enthalpy of formations, dipole and energy of molecular orbitale HOMO and LUMO energies levels are calculated for all pollutants and the three surface active materials.